CHANGE OF DEEP CENTERS DURING OPERATION ALGAAS LIGHT EMITTING DIODES - Abdullaev Jamolitdin Solijonovich (Western European Studies, 2024)
Light-emitting diodes (LEDs) are widely used in optoelectronics. In this regard, studying the degradation process of LEDs, that is, changes in their parameters during operation, is an urgent task both from the point of view of elucidating the physics of elementary processes causing degradation and their mechanisms, and to improve the reliability of devices. The paper presents the results of a study of the degradation process of LEDs based on Al Ga As:Te(x 0,34) Al Ga As:Zn-GaAs:Zn x x 1 0,34 0,66 − − heterostructures obtained by liquidphase epitaxy. When studying the degradation phenomenon, along with classical methods of studying electroluminescence spectra in the temperature range 77-300K, capacitance-voltage and current-voltage characteristics, modern highly informative methods were used.
Keywords: light-emitting diodes; liquid-phase epitaction; photoluminescence